2017
DOI: 10.1371/journal.pone.0174716
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and antimicrobial susceptibility of Clostridium difficile isolates from two Korean hospitals

Abstract: Clostridium difficile is one of the main etiological agents causing antibiotic-associated diarrhea. This study investigated the genetic diversity of 70 toxigenic C. difficile isolates from two Korean hospitals by employing toxinotyping, ribotyping, multilocus sequence typing (MLST), and pulsed-field gel electrophoresis (PFGE). Toxin gene amplification resulted in 68 A⁺B⁺ and two A-B+ isolates. Most isolates (95.7–100%) were susceptible to daptomycin, metronidazole, and vancomycin. Seventy C. difficile isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…ST2, all classified as RT014/020, was the second most common strain. This finding is also in accordance with previous studies which indicates RT014/020 as a worldwide disseminated ribotype (Sundram et al, 2009;Weber et al, 2013;Yan et al, 2013;Cheng et al, 2015;Kuwata et al, 2015;Nicholas et al, 2017).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…ST2, all classified as RT014/020, was the second most common strain. This finding is also in accordance with previous studies which indicates RT014/020 as a worldwide disseminated ribotype (Sundram et al, 2009;Weber et al, 2013;Yan et al, 2013;Cheng et al, 2015;Kuwata et al, 2015;Nicholas et al, 2017).…”
supporting
confidence: 93%
“…Of these six novel STs, four were also identified as new ribotypes ( Table 1). The diversity found in the present study seems to be higher than previously reported in other hospitals elsewhere (Weber et al, 2013;Kuwata et al, 2015;Cheng et al, 2015;Nicholas et al, 2017;Wang et al, 2017;Chen et al, 2018). Some studies have showed a link between the high diversity of ribotypes and less occurrence of CDI by RT027 and RT078 (Freeman et al, 2015;Rodriguez et al, 2016).…”
contrasting
confidence: 59%
“…For example, in Korea and Japan, ST17 is the predominant type (55.7% and 21.5%, respectively), followed by ST2 (8.6% and 10.0%, respectively). 30 , 31 However, in Europe, RT027/ST1 is the most prevalent genotype, especially in Western and Eastern Europe. 32 …”
Section: Discussionmentioning
confidence: 99%
“…• Increased inflammation C. difficile RTs are geographically distributed by nation and region, but also by hospital. 103 The population of C. difficile RTs is expansive, but dominated by a few RTs, and population balance changes over time. 104,105 A few major strains, as follows, are dominant: BI/NAP1/027, 014, 001/072, and 078 predominated in a population of 99 RTs identified in European stool samples.…”
Section: Emerging Strains and Epidemic Ribotypesmentioning
confidence: 99%